Biochemical analysis of the BTG1 variants associated with Non-Hodgkin’s lymphoma - Almasmoum, Hibah (2017)
Non-Hodgkin’s lymphoma (NHL) is a group of lympho-proliferative disorders characterised by genetic mutations resulting in the selection of a malignant clone. Recently, mutations in the anti-proliferative B-cell translocation 1 gene (BTG1) and B-cell translocation 2 gene (BTG2) have been identified in in NHL cases, which suggests a direct involvement of BTG1 and BTG2 in malignant transformation. BTG1 and BTG2 are members of the human BTG/TOB family. They are characterised by the conserved amino-terminal BTG domain, which mediates interactions with the human Caf1(hCaf1) catalytic subunit of the Ccr4-Not deadenylase complex .In addition, the BTG domain binds to the cytoplasmic poly (A)-binding protein (PABPC1). This complex plays a critical role in mRNA deadenylation and degradation as well as translational repression. It is currently unclear how, or indeed whether, mutations in BTG1 and BTG2 affect the function of the gene products. Therefore, a combination of sequence analysis and molecular modelling was used to predict the functional consequences of mutations previously identified in NHL. Sorting intolerant from tolerant (SIFT) and Suspect (Disease-Susceptibility-based SAV Phenotype Prediction) prediction tools enabled the identification of amino acid residues that would potentially interfere with the protein function, and hence may be associated with disease. In total 45 mutations in BTG1 and BTG2 were assessed. These mutations were derived from NHL samples, including diffuse large B-cell lymphoma (DLBCL), follicular lymphoma and Burkitt's lymphoma. Of the variants analysed, 15 were predicted to interfere with the function of BTG1 using SIFT analysis (Score ≤0.05). Only seven of these variants were predicted to be likely associated with disease using Suspect algorithm (Score ≥50), and an additional variant, BTG1 C149del, was predicted to interfere with protein function using PROVEN (Protein Variation Effect Analyzer). The ability of these protein variants to interact with known partners was established using yeast two hybrid assays. In addition, functionally assessment of the role of the mutated proteins in cell cycle progression, translational repression and mRNA degradation was also performed. Using a yeast two-hybrid system, ten BTG1 variants were shown to affect the interaction of BTG1 with the hCaf1 (CNOT7/CNOT8) catalytic subunit of the Ccr4-Not deadenylase complex. In addition, when BTG1 variants were transfected into mammalian cells, these BTG1 variants (M11I, F25C, R27H, F40C, P58L, G66V, N73K and I115V), unlike the wild-type proteins, were not able to inhibit cell cycle progression. These results suggest that anti-proliferative BTG1 is required for hCaf1 (CNOT7/CNOT8) deadenylase activity. The remaining BTG1 variants (L37M, L94V, L104H and E117D) were not consistent in the correlation of BTG1 interaction with hCaf1 (CNOT7/CNOT8) and inhibition of cell growth which led to the suggestion that BTG1 may require an additional factor such as PABPC1. Interestingly, several BTG1 variants (M11I, F25C, R27H, P58L, N73K I115V and E117D) did not require interaction with the hCaf1 (CNOT7/CNOT8) deadenylase enzyme to reduce reporter activity as established using 3’ UTR tethering assays. This suggests that BTG1 may also have a role in regulating cell cycle progression and RNA degradation via Ccr4-Not deadenylase complex independent mechanisms. The data show that variants in BTG1 commonly found in DLBCL, are functionally significant and are likely to contribute to malignant transformation and tumour cell grow.